Aesthetic visions of mural painting in international airports (A Proposal of experience for the researcher at the Yemeni airports): (A Proposal of experience for the researcher at the Yemeni airports) - Mohammed Maqbool, Hayat; Elmasry, Nermen; Mohamed Nour, Zeinab (International Journal of Scientific Research and Management (IJSRM), 2021)
Purpose: This work is a trial study for International Airports esthetics developments. The work was introduced to explore the disparity and activities of that airports as well as its benefit to tourism growth internationally. All that in order to give a clear understanding and appreciation of the importance of mural and artistic works in the architecture of international airports, all of which are beneficial to the aesthetic, visual, technical and psychological benefits of travelers and visitors, as well as the benefits to tourism and culture of the country in which there are airports.Materials and methods: The practical experience of the researcher is based on three main axes, through which it deals with some aspects of the Yemeni environment to be applied within some of the wall works in Yemen airports.  All murals are decorated with glass mosaic materials and ceramics on large wooden panels. The 1st axis: murals inspired by the ancient heritage of Yemeni architecture. The 2nd axis: Murals inspired by the picturesque Yemeni nature. The 3rd axis: murals inspired by the social and psychological state of the Yemeni human being.Conclusion:  Many Yemeni institutions' buildings are decorated with murals, paintings, and other subjects related to that region or community. We note that the government of Yemen has taken care of this type of architecture, such as the art of murals.Recommendations: The mural art works are not suitable for placing in international airport halls except with basic points that are supposed to be taken into account in the mural work to be placed inside airports, where it is recommended to take into account the three main axes: the environment, the design, and the materials in which these murals were completed.Keywords: mural, airports, Yemeni airports, esthetics.